(untitled) (GYMNASIUM, 2017)
Reaching sports performance in a sports branch, discipline or event is dependent and conditioned also by the social context, the demographic situation of the area, region, the athlete’s country, age, gender or race, experience and the “migration of the sports population” etc. Previous research has shown that statistics can provide evidence in sport on the dynamics over a certain period of time, but statistics can also be a benchmark for future predictions. This paper aims to highlight various statistical analyses, for a period of 101 years, based on various criteria that have contributed more or less to the “record” of national titles in a distinct region of Romania, namely Bacau County. The research subjects are represented by 162 performance athletes registered according to the Romanian Athletics Federation regulations into four age categories (Junior II, Junior I, Youth and Senior) and into two gender categories (male, female). By comparing the results highlighted by the analysis of 712 titles, we can declare that the dynamics of sports performance over a century of athletics in Bacau can be clearly traced only by analyzing the data as a whole. The results, reported in detailed analyses of certain criteria, illustrate trends which do not allow us to generalize.